Identifying the foci for nursing in Irish intellectual disability services - SHEERIN, FINTAN (My University, 2004)
Many of the attempts to classify nursing phenomena (or diagnoses) have been developed within the context of acute/chronic general nursing, and may , as such, be seen to represent only a subsection of the profession as a whole, for scant consideration has been made of the phenomena of interest to intellectual disability nurses. This may be because such nurses have traditionally been located in only a handful o f countries, and have not been motivated to examine this area themselves. Considering that intellectual disability nursing in Ireland , is at a crucial juncture, with various forces, within and outside of nursing seeking to relegate it to a post-graduate, specialist level, there is a risk that the specific input of this nursing will be lost, and will be subsumed within an illness/problem-oriented approach, that is not representative of the reality of care in this field. The purpose of this study was to identify the foci of interest that are specific to nursing intervention within residential, intellectual disability nursing. This was achieved through the use of a Delphi study which was followed up by three focus groups held among Irish intellectual disability nurses working in three service settings, and personal interviews with residential service/nurse managers.
PUBLISHED
Keywords: Intellectual disability; nursing diagnosis; nursing focus; Delphi; focus groups; Making Ireland